2020
DOI: 10.1002/adfm.202002982
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Spider Silk Forms Tough and Elastic Nanomembranes that are Protein‐Permeable and Support Cell Attachment and Growth

Abstract: Biologically compatible membranes are of high interest for several biological and medical applications. Tissue engineering, for example, would greatly benefit from ultrathin, yet easy‐to‐handle, biodegradable membranes that are permeable to proteins and support cell growth. In this work, nanomembranes are formed by self‐assembly of a recombinant spider silk protein into a nanofibrillar network at the interface of a standing aqueous solution. The membranes are cm‐sized, free‐standing, bioactive and as thin as 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…The structural rearrangement of silk proteins to form a nanofibrillar membrane corresponds to a continuous reduction of α-helices in favor of increased β-sheet conformations. 34 The content of β-sheet formation has previously been reported to account for the extensibility of silk proteins, 35 as well as the unfolding and elasticity of, for example, fibrin. 36 The membranes can be lifted from the interface by lowering the custom-made 3D-printed holder ( Figure S1 ) and allowing the membrane to detach from the walls of the well and instead adhere to the holder.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structural rearrangement of silk proteins to form a nanofibrillar membrane corresponds to a continuous reduction of α-helices in favor of increased β-sheet conformations. 34 The content of β-sheet formation has previously been reported to account for the extensibility of silk proteins, 35 as well as the unfolding and elasticity of, for example, fibrin. 36 The membranes can be lifted from the interface by lowering the custom-made 3D-printed holder ( Figure S1 ) and allowing the membrane to detach from the walls of the well and instead adhere to the holder.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of the membrane can be altered by varying the silk concentration or the assembly time. 34 Noteworthily, the thickness of the silk membranes increases over time, from 470 ± 110 nm at day 0 to 690 ± 150 nm at day 7, by keeping them submerged in cell culture media ( Figure S2 ). The serum and growth factor components in the media adsorb onto each side of the silk membranes, thereby adding particular bioactive properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…102 What's more, a novel and simple method to produce silk came true by forming a film in air-liquid interface. 105,106 At the same time, the postprocessing of spider silk can also improve the performance of spider silk to a certain extent. 107 Studies on the forms of spider silk protein showed that controlled and characteristic carriers can be obtained by making spider silk into spheres, 108 which can be made into microspheres, 109,110 capsules, 30 particles, 27 foam, 111 films and hydrogels.…”
Section: Artificial Spider Silk Proteinmentioning
confidence: 99%